Особливості перебігу вагітності та пологів, стан фетоплацентарного комплексу при багатоплідній вагітності, залежно від типу плацентації - Бабінчук, Олена Василівна; Babinchuk, O. V. (Запорізький державний медичний університет, 2018)
В роботі здійснено ретроспективний аналіз 80 історій пологів жінок з багатоплідною вагітністю (БВ); обстежено 155 вагітних, з яких 114 – з БВ і 41 – з одноплідною вагітністю; проведено апробацію розробленої моделі прогнозування ризику ускладнень серед 27 жінок з БВ; визначено ефективність створених індивідуалізованих підходів до ведення пацієнток з БВ в 25 жінок. Встановлено, що більшість жінок з БВ мають обтяжений соматичний і гінекологічний анамнез, перебіг вагітності та пологів у них супроводжується частим розвитком ускладнень, наслідком чого є зростання відсотка оперативних втручань та несприятливих перинатальних наслідків. На підставі поглибленого дослідження фетоплацентарного комплексу з визначенням плацентарного лактогену, естріолу, прогестерону та кортизолу при БВ визначено особливості його функціонування при різних типах плацентації. The thesis is devoted to the problem of multiple pregnancy (MP), improvement of perinatal outcomes on the basis of studying the features of its course and childbirth, depending on the type of placentation, optimization of the diagnostic algorithm in the antenatal period. Retrospective analysis of 80 cases of delivery of women with MP was conducted and 155 pregnant women were prospectively examined, 114 of which were with MP, and 41 were with singleton. Retrospective analysis of 80 cases of delivery of women with MP was conducted and 155 pregnant women were prospectively examined, 114 of which were with MB, and 41 with singleton; approbation of the developed model were carried out on 27 women with MP. It is established that women with MP in the majority have a weighed somatic and gynecological anamnesis, pregnancy and childbirth are accompanied by frequent complications development, which results in an increase in the percentage of surgical interventions and adverse perinatal outcomes. Based on the in-depth study of the feto-placental complex in multiple pregnancies with the determination of placental lactogen, estriol, progesterone and cortisol, multiple pregnancies are supplemented and the features of its functioning are clarified for various types of placentation. For the purpose of early prognosis, based on the obtained data, a prognostic model was developed for calculating the integral risk index for the development of gestational and perinatal complications in MP and clinically significant factors of perinatal complications in multiple pregnancy were determined. It has been established that prenatal factors, multiple pregnancy in anamnesis, fetal growth retardation syndrome and premature rupture of the membranes have the greatest impact on the state of newborns.
Peculiarities of pregnancy and delivery progress, the state of the fetoplacental complex in case of multiple pregnancy depending on the type of placentation
Keywords: багатоплідна вагітність; гормони; матково-плацентарно-плодовий кровоток; новонароджені; прогностичні фактори; multiple pregnancy; hormones; utero-placental-fetal blood flow; newborns; prognostic factors